Concrete implantable bar enabled smart sensing technology for structural health monitoring. (May 2023) - Yang, Ziqian; Li, Yang; Sang, Xiaohan; Ding, Yewei; Ma, Bin; Chen, Qingjun; Kong, Qingzhao
Abstract: This work proposes a concrete implantable bar (CIB) enabled smart sensing technology for the detection of concrete beam damage. Instead of the conventional technique that posts the sensors on the host structure externally or embeds them inside the concrete before casting, this developed technology enables an implantable manner to install specially designed sensors with unique stable and replaceable functions. The CIB integrates a line array of tubular piezoceramic shells (TPSs) that can excite and receive probe signal in concrete. The working principle of this CIB was explained theoretically, and its basic performance regarding the conversion efficiency between the input and output signals was investigated numerically. To assess the structural state comprehensively, a singular value decomposition (SVD)-based wavelet packet algorithm was adopted. This algorithm relied on the classical wavelet packet analysis to construct an energy matrix at a certain frequency band, and then revealed the structural damage degree using the singular values of this matrix. The feasibility of the proposed methods was verified using a reinforced concrete (RC) beam specimen subjected to a four-point bending test, wherein a pair of CIBs, one as an actuator and another as a sensor, were implanted in the beam to sample data from different loading processes. The assessment results using the SVD-based algorithm well characterize the beam state throughout the loading process; and show higher accuracy than those using a convention method in this continuous monitoring case.